2012
DOI: 10.1111/j.1365-313x.2012.04930.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of leaf‐type ferredoxin‐NADP+ oxidoreductase results in the permanent induction of photoprotective mechanisms in Arabidopsis chloroplasts

Abstract: SUMMARYArabidopsis thaliana contains two photosynthetically competent chloroplast-targeted ferredoxin-NADP + oxidoreductase (FNR) isoforms that are largely redundant in their function. Nevertheless, the FNR isoforms also display distinct molecular phenotypes, as only the FNR1 is able to directly bind to the thylakoid membrane. We report the consequences of depletion of FNR in the F 1 (fnr1 · fnr2) and F 2 (fnr1 fnr2) generation plants of the fnr1 and fnr2 single mutant crossings. The fnr1 · fnr2 plants, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…S1). These results are in line with the previous finding showing that inactivation of the two A. thaliana leaf‐type FNR isoforms is lethal (Lintala et al ), further supporting the view that FNRL does not have redundant function(s) with leaf‐type FNRs. It remains to be seen whether principle function of FNRL is as a diaphorase, oxidising NADPH and reducing a specific metabolite, or whether it has protein electron transfer partners.…”
Section: Discussionsupporting
confidence: 92%
“…S1). These results are in line with the previous finding showing that inactivation of the two A. thaliana leaf‐type FNR isoforms is lethal (Lintala et al ), further supporting the view that FNRL does not have redundant function(s) with leaf‐type FNRs. It remains to be seen whether principle function of FNRL is as a diaphorase, oxidising NADPH and reducing a specific metabolite, or whether it has protein electron transfer partners.…”
Section: Discussionsupporting
confidence: 92%
“…Under fluctuating light conditions the stn7 mutant demonstrated a remodelling of the PETC by a reduction in the amount of PSI [24,25]. Similar phenotype has been observed also in other mutants affected in proteins of the acceptor side of PSI [26]. Possibly, the limitation in the electron flow from PSI observed in the rao1 mutants could be explained by a more reduced stroma and lower availability of oxidized electron acceptors.…”
supporting
confidence: 72%
“…Consistent with this, in gpt2 plants fewer Cyt b 6 f , plastocyanin, ATP synthase and FNR peptides were increased significantly at HL. Various studies have shown the Cyt b 6 f complex, ATP synthase and FNR to be important in determining capacity for both electron transport and carbon fixation (Price et al, 1998; Ruuska et al, 2000; Yamori et al, 2011; Lintala et al, 2012). These data suggest that the ability of gpt2 plants to acclimate the PETC to HL is impaired compared to the WT.…”
Section: Discussionmentioning
confidence: 99%